RADIOGRAPHIC DIAGNOSIS OF INTERNAL AND EXTERNAL ROOT RESORPTIONS (International Seven Journal of Multidisciplinary, 2026)
Root resorption corresponds to the progressive loss of mineralized dental tissues and may occur in a physiological, pathological, or idiopathic manner. This resorption can affect both the internal and external surfaces of the tooth, presenting different etiological mechanisms, radiographic patterns, and therapeutic implications. Early diagnosis is crucial for the prognosis of the dental element and for defining the most appropriate clinical approach; however, diagnosis often occurs sporadically during routine clinical and radiographic examinations, making a favorable prognosis more difficult. Conventional radiographs, such as periapical and panoramic images, are widely used as initial evaluation methods; nevertheless, because they are two-dimensional examinations, they present important limitations, including structural overlap, distortions, and low sensitivity for early lesions, with computed tomography being the most satisfactory examination for diagnosing this condition. This study is characterized as a narrative literature review, conducted through a systematized survey of scientific literature in the PubMed, Scopus, and Web of Science databases, using the descriptors “Tooth Resorption,” “Root Resorption,” “Radiography,” and “Diagnosis,” combined with Boolean operators; articles published in the last five years, available in full text and directly addressing the use of radiographic methods in the diagnosis of internal and external root resorptions were included, while duplicate studies, isolated case reports, and publications lacking methodological rigor were excluded. The selection process occurred in stages, including the reading of titles and abstracts and the critical analysis of full texts. The results demonstrate that Cone Beam Computed Tomography presents greater sensitivity and specificity compared to conventional radiographs, enabling detailed three-dimensional visualization, better differentiation between types of resorption, and volumetric analysis of root loss, leading to the conclusion that CBCT is a fundamental tool for the diagnosis and monitoring of root resorptions, especially in complex cases involving recovery and orthodontic movement.